Transformasi Industri Keuangan Dan Perdagangan Melalui Fintech Dan E-Commerce: Studi Analisis Dampak Dan Tantangan - Hilda; Gusti, Girang Permata (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) IBE Indonesia, 2024)
This research aims to analyze the transformation of the finance and trade industry triggered by the adoption of fintech and e-commerce, as well as identify the impacts and challenges faced by companies and consumers in this digital era. The research method used is a literature review and descriptive study using secondary data. The results of the analysis show that fintech and e-commerce have brought significant changes in the financial and trade sectors, including financial service innovation, financial inclusivity, and shopping efficiency. The research identifies challenges such as data security, complex regulation, and intensifying competition in the digital marketplace. To face this challenge, companies and businesses need to design the right strategy in adopting digital technology, establish partnerships with technology companies, improve human resource capabilities, and pay attention to regulations and data security. This research provides deep insights into the transformation of the finance and commerce industry in the era of fintech and e-commerce, and provides guidance for companies and regulators in creating a safe and profitable environment in the digital age.